The Analysis of Amount and Various Age of Productive Female Bali Cattle that Slaughtered at Abbatoirs - I Wayan Suardana; I Made Sukada; I Ketut Suada; Dyah Ayu Widiasih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Abstract Base on the ability for surviving at the limited vegetations, bali cattle is famous as a pioneer cattle. Although the fertility of Bali cattle has known so high (up to 80%), but the slaughter of productive female of bali cattle from year to year is so high too, so that the existance of Bali cattle in the future is threatened extinct. The accurate data indicating the amount of Bali cattle slaughtered at the abbatoirs are not available yet, exactly from the Pesanggaran and Mambal abbatoirs as the bigger abbatoirs in Bali. The study used 246 heads of Bali cattle originated from Pesanggaran, and 232 heads of Bali cattle originated from Mambal abbatoirs, respectively. The study indicated as many as 81,7%, and 87,5% of Bali cattle slaughtered at those abbatoirs were female. According to their ages, most of them were productive too, i.e. 99% at Pesanggaran, and 67,49% at Mambal abbatoirs, respectively. These result indicated it is needed a special attention from the Bali government exactly from the Animals Husbandry Officer in order to prevent the loss of Bali cattle populations in the future.